Vibrational relaxation of NO (v = 1-16) with NO, N2O, NO2, He and Ar studied by time-resolved Fourier transform infrared emission. - Hancock, G; Morrison, M; Saunders, M (2009)
Rates of vibrational quenching of NO (v = 1-16) in collisions with a series of quenching species NO, NO2, N2O, He and Ar have been measured at 295 K. NO (v) was formed both by the O(1D) + N2O reaction and the 193 nm photolysis of NO(2), and time-resolved FTIR emission was used to follow the behaviour of the vibrationally excited species. The trends in quenching rate constants can be explained in terms of V-T transfer, V-V transfer and by the effects of competing processes. He and Ar show trends expected from SSH theory, but with relaxation rates that are considerably higher than those expected from previous studies with closed shell molecules, and the influence of non-adiabatic pathways in the relaxation of the NO 2Pi state is discussed. Relaxation with NO2 shows the influence of resonant energy transfer to the nu3 mode, with rate constants peaking at v = 10. For N2O, relaxation rates show essentially a linear increase with v. A linear increase is expected for the change of the transition moment with v for the harmonic oscillator approximation, and when this is taken into account the "reduced probabilities" (defined as P/v, where P is probability of a gas kinetic collision changing the vibrational level from v to v-1) are approximately independent of the energy lost in the NO molecule. The influence of complex formation far from resonance is invoked in both this and for quenching of low vibrational levels by NO2. Finally, self-quenching shows rates which initially decrease with increasing v, but then show a marked increase, with a minimum value at v = 9. Both V-V and V-T processes are believed to occur. Where previously published data are available, general agreement is observed in this study.